Mutant p53 Drives Cancer by Subverting Multiple Tumor Suppression Pathways - Haupt, Sue; Raghu, Dinesh; Haupt, Ygal (Frontiers in Oncology, 2016)
The tumour suppressor p53 normally acts as a brake to halt damaged cells from perpetrating their genetic errors into future generations. If p53 is disrupted by mutation, it may not only lose these corrective powers, but counter-productively acquire new capacities that drive cancer. A newly emerging manner in which mutant p53 executes its cancer promoting functions is by harnessing key proteins (including many transcription factors), which normally partner with its wild type, tumour-inhibiting counterpart. In association with the subverted activities of these protein partners, mutant p53 is empowered to act across multiple fundamental cellular pathways (regulating cell division and metabolism) and corrupt them to become cancer promoting.